Group Identification and Support for the Supreme Court: Evidence from Evangelical Protestants - Kromphardt, Christopher D. (Journal for the scientific study of religion, 2019)
Research on the determinants of the U.S. Supreme Court's institutional support among the public focuses on three factors at the level of the individual, including satisfaction with its performance, knowledge of the judiciary, and support for democratic values. Evidence from the group level has revealed that the relative importance of these factors can vary, despite the predictions of positivity theory that the effects of all factors should be similar across all subsets of the U.S. population. We seek to explain this inconsistency between theory and evidence through an analysis of evangelical Protestants, a politically powerful and theoretically compelling group. Drawing on group-based studies, we develop a principled account of when group members will base their institutional support more strongly than others do on their satisfaction with the Court's recent performance, and identify defining features of the information environment of evangelical Protestants that satisfy the model's components. We report evidence from a national survey that the effects of all three major factors differ systematically for evangelical Protestants. We discuss implications of our analysis for an ongoing debate over positivity theory and for identifying other groups for whom institutional and specific support will be strongly linked.